Improving Policy Coordination Across the Water, Energy, and Food, Sectors in South Asia: A Framework - Rasul, Golam; Neupane, Nilhari (Frontiers in Sustainable Food Systems, 2021)
Land, water, and energy resources are coming under unprecedented pressure owing to growing populations, urbanization, industrialization, and changing lifestyles, food habits, and climate. Generally, sectoral approaches are taken to address these challenges that overlook the close linkages between the water, energy and food sectors and resultant cross-sectoral implications. The result is an uncoordinated and unsustainable use of resources that increasingly threatens water, energy, and food securities in many parts of the world. To enhance sustainability in resource use, the use of water-energy-food nexus (WEF) approach has been advocated in recent years. Despite its conceptual appeals, the practical application of this approach in government planning and decision making has remained limited in part due to lack of an appropriate framework to operationalize the concept as a planning and decision-making tool. This paper suggests a framework for operationalizing the nexus concept in planning and decision-making, using South Asia as an example. The framework outlines four steps to evaluate and prioritize nexus issues to improve cross-sectoral planning and coordination using three broad criteria to assess the impact of actions in one sector on another: synergies (co-benefits), trade-offs (externalities), and neutrality. A cross-sectoral coordination body provides the institutional mechanism for ensuring coordination of policy and action. The four steps are: (a) harmonizing policy goals, (b) identifying interactions and critical connections between these sectors in an integrated manner, (c) assessing compatibility of nexus objectives and policy instruments, and (d) screening programs, projects, and investments against nexus goals. The framework is expected to help governments in coordinating the actions of diverse actors across the water, energy and food sectors and designing policies and programs that address trade-offs, while increasing production sustainably, conserving natural resources, and enhancing -water-energy-food nexus outcomes.